A rare development of basal cell carcinoma on trichoepithelioma in a chemical burn scar tissue: A case report. Issue 38 (September 2018) - Kim, Seong Hwan; Kim, Dong Wan; Hwang, Jae Ha; Kim, Kwang Seog; Lee, Sam Yong
Abstract: Rationale: Trichoepithelioma (TE) is a rare benign skin tumor that originates from the hair follicle epithelium. Although skin lesions arising from scar tissues are mostly malignant, the development of a benign tumor such as TE is a rare event. Patient concerns: A 28-year-old male patient who had a scar on the left cheek which arose 10 years ago because of a chemical burn visited our hospital. Scar revision was performed under local anesthesia. Diagnosis: Histological examination identified the specimen as a TE with malignant foci suspicious of basal cell carcinoma (BCC) at the lateral margin of the specimen. Interventions: A second stage operation was planned to excise the BCC with a 4 mm margin of the normal skin around the previous lesion. Outcomes: No complication or recurrence was noted during the 1-year follow-up period after surgery, and the appearance of the scar improved. Lessons: The correct differential diagnosis between TE and BCC is very important. So follow up at regular intervals is recommended for evaluation of recurrence or transformation into BCC in patients with tumors arising from chemical burn scars. And the concomitant development of TE and BCC should also be considered from a chemical burn scar.